Migrants' Missing Votes - Yvonne Giesing; Felicitas Schikora (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Emigrants are less likely to participate in elections in their home country. They are also self-selected in terms of education, gender, age, and political preferences, changing the structure of the origin population. High emigration rates can therefore have a systematic influence on election results. Using administrative migration and voting data, we show that counties in Poland that have experienced large emigration following the accession to the European Union in 2004 are characterised by larger vote shares for right-wing parties. We use instrumental variable estimations that exploit distance to the border and to airports to account for endogenous migration patterns. Results are robust to estimations using first differences. Results hold for elections of the national and EU parliament and for different areas within Poland. Surprisingly, we find no effects on incumbent parties. In addition, our results show increased voting for parties with pro-European positions. Analysing the mechanisms using survey data, we illustrate that emigrants (stayers) have less (more) trust in right-wing parties. The results have important policy implications for voting regulations.
Keywords: D72; F22; O15; P16; 330; migration; voting; political economy; EU enlargement; trust